ANALISIS KESESUAIAN DAN DAYA DUKUNG LOKASI BUDIDAYA KERANG MUTIARA MABÈ (Pteria penguin) DI PERAIRAN PALABUSA KOTA BAU-BAU - Hartina Iyen; Muhammad Kasnir; Hamsiah Hamsiah (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2021)
Southeast Sulawesi region, especially the Palabusa waters area of Buton Regency, has become a center for cultivation of several economical species, one of which is the mabè pearl (Pteria penguin). This research was conducted with the aim of identifying the suitable area for the development of mabè pearl cultivation and determining the carrying capacity of the area in Palabusa waters in developing mabè pearl cultivation. This research was conducted in September to November 2020. The data collection was carried out in two parts, namely field and laboratory activities. The data obtained then were analyzed descriptively. The results of this study indicate that: (1) Physical, chemical and biological parameters in Palabusa waters indicate the potential site suitability for the development of mabè pearl cultivation are in the very suitable category (SS) is 128, 3 Ha, quite suitable (S) is 64,5 Ha and not suitable (N) is 47,7 Ha for mabè pearl cultivation; (2) The carrying capacity of Palabusa waters for the development of pearl mabè pearl culture is 847 units. Further research needs to be carried out, especially regarding social and economic aspects as well as other water quality parameters that affect the determination of the suitability of mabè pearl cultivation areas such as environmental pollution, waves and tides.